2004
DOI: 10.1093/ejo/26.5.469
|View full text |Cite
|
Sign up to set email alerts
|

Effects of local administration of clodronate on orthodontic tooth movement and root resorption in rats

Abstract: Clodronate, a non-N-containing bisphosphonate, strongly inhibits bone resorption and also has anti-inflammatory properties. The purpose of this study was to examine the effect of the local administration of clodronate on orthodontic tooth movement. Both the right and left upper first molars of 26 7-week-old male Wistar rats were moved buccally with a standardized expansion spring. Clodronate solution was injected into the sub-periosteum area adjacent to the left upper molar every third day during the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 31 publications
7
72
0
2
Order By: Relevance
“…In vitro and in vivo studies have demonstrated that various bb modulate the release of proinflammatory mediators (9,10) and inhibit PGE 2 synthesis induced by phlogistic or mechanical stimuli (13,18,19). These studies postulate that the inhibition of endogenous PGE 2 production may be involved in the mechanism of action of bb (20).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In vitro and in vivo studies have demonstrated that various bb modulate the release of proinflammatory mediators (9,10) and inhibit PGE 2 synthesis induced by phlogistic or mechanical stimuli (13,18,19). These studies postulate that the inhibition of endogenous PGE 2 production may be involved in the mechanism of action of bb (20).…”
Section: Discussionmentioning
confidence: 98%
“…Prostaglandins are an important part of this mechano-biochemical signalling (15)(16)(17). Stress-induced PGE 2 release has been well-investigated in vitro study, suggesting an activation mediated by the inducible COX-2-catalyzed pathway (18). It is well known that in OI, the genetic defect in the osteoblast interferes with the multiple mechanisms that normally ensure adaptation of the skeleton to the increasing mechanical need during growth (7).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Bisphosphonates have been the most common prescribed medications for osteoporotic patients [4][5][6] and their effects on orthodontic tooth movement have been investigated in rat model. [7][8][9][10] Essentially, bisphosphonates are internalized into osteoclasts leading to inhibition of bone resorption and induction of osteoclast apoptosis. [11][12][13] ZOL is a potent and novel bisphosphonate that has been recently shown to significantly reduce fracture risk in the patients who received once-yearly dosing regimen for the treatment of postmenopausal osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Borah et al 5 evaluated changes in bone mineralization and architecture in postmenopausal women with osteoporosis after long-term treatment with risedronate, elucidating normalization of mineral levels. The effect of bisphosphonates on orthodontic tooth movement (OTM) has also been investigated in some reports, [6][7][8][9][10] in which administration of bisphosphonates decreased OTM.…”
mentioning
confidence: 99%